1989
DOI: 10.1164/ajrccm/139.3.759
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Hyaluronic Acid in the Alveolar Interstitial Tissue in Bleomycin-induced Alveolitis

Abstract: By using biotin-labeled proteoglycan core protein and an avidin-enzyme system, hyaluronic acid (HA) was visualized in the lungs of rats at different times (4, 10, and 20 days) after bleomycin injury. Four days after an intratracheal injection of bleomycin, HA was accumulated in the edematous alveolar septa of the focal areas with lung tissue injury. An interstitial cellular infiltrate of mainly lymphocytes was present. In normal rat lung, HA was not seen in the alveolar tissue but confined to peribronchial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 5 publications
7
91
1
Order By: Relevance
“…In human ARDS increased concentrations of hyaluronan in bronchoalveolar lavage fluid (BAL) has been found [27], and in a porcine model of sepsis-induced lung injury resembling ARDS, accumulation of interstitial hyaluronan has been seen [19]. This is in analogy to the increased amounts of hyaluronan found both interstitially and in BAL fluid in other interstitial inflammatory pulmonary diseases such as sarcoidosis and allergic alveolitis [28,29,30]. Possibly, more knowledge of the changes in pulmonary interstitial hyaluronan metabolism in relation to sepsis may provide new information on the pathophysiology of ARDS development.…”
Section: Hyaluronan and Oedema Developmentmentioning
confidence: 99%
“…In human ARDS increased concentrations of hyaluronan in bronchoalveolar lavage fluid (BAL) has been found [27], and in a porcine model of sepsis-induced lung injury resembling ARDS, accumulation of interstitial hyaluronan has been seen [19]. This is in analogy to the increased amounts of hyaluronan found both interstitially and in BAL fluid in other interstitial inflammatory pulmonary diseases such as sarcoidosis and allergic alveolitis [28,29,30]. Possibly, more knowledge of the changes in pulmonary interstitial hyaluronan metabolism in relation to sepsis may provide new information on the pathophysiology of ARDS development.…”
Section: Hyaluronan and Oedema Developmentmentioning
confidence: 99%
“…During the experimental induction of bleomycin-induced alveolar injury in the rat there is a considerable accumulation of high molecular HYA in the oedematous interstitial alveolar space during the alveolitis phase [22,23,24], which has been attributed to alveolar interstitial fibroblast-like cells [24]. Experimental studies have also demonstrated a link between the alveolar and interstitial accumulation of HYA and the intraalveolar oedema and oedema of the fragile alveolar structure [25].…”
Section: Pulmonary Conditionsmentioning
confidence: 99%
“…Hyaluronan turnover and degradation increase during inflammation, and lower molecular mass species of hyaluronan accumulate. Importantly, this accumulation is detected prior to the influx of inflammatory cells and deposition of collagen, which suggests that low molecular mass hyaluronan accumulation is an early event in the development of inflammatory pulmonary disease (4). Although the mechanisms of hyaluronan turnover and degradation are still unknown, it is generally accepted that free radicals, especially the highly reactive hydroxyl radical, play an important role in the degradation process of hyaluronan (5,6).…”
mentioning
confidence: 99%